2019
DOI: 10.1590/1984-70332019v19n4c69
|View full text |Cite
|
Sign up to set email alerts
|

SCS426 Venice: new apple cultivar with glomerella leaf spot resistance and picking time in March

Abstract: SCS426 Venice was developed by hybridization between Epagri 404-Imperatriz (♀) and Epagri 406-Baronesa (♂), performed at the Epagri Experimental Station in Caçador, SC, Brazil, in 2001. It requires less winter chilling than 'Gala' and 'Fuji' traditional clones, whose fruit is picked in March. It is resistant to glomerella leaf spot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
3
2
0
1
Order By: Relevance
“…It is observed in Table 3 that the cultivars Venice, Elenise and Isadora follow the expected segregation pattern for all markers amplified in PCR considering the genotypes of male and female parents, respectively, as reported in the literature (Denardi et al 2019a, 2019b, Denardi et al 2023. However, for the cultivar Luiza, of the 19 evaluated genome regions, only 9 regions followed the expected pattern of allele segregation, showing the presence of only one allele common to the Cripps Pink cultivar, previously described as the male parent.…”
Section: Tl Brancher Et Alsupporting
confidence: 71%
See 2 more Smart Citations
“…It is observed in Table 3 that the cultivars Venice, Elenise and Isadora follow the expected segregation pattern for all markers amplified in PCR considering the genotypes of male and female parents, respectively, as reported in the literature (Denardi et al 2019a, 2019b, Denardi et al 2023. However, for the cultivar Luiza, of the 19 evaluated genome regions, only 9 regions followed the expected pattern of allele segregation, showing the presence of only one allele common to the Cripps Pink cultivar, previously described as the male parent.…”
Section: Tl Brancher Et Alsupporting
confidence: 71%
“…In the grouping dendrogram made from the dissimilarity data matrix calculated between cultivars for the 19 SSR markers (Figure 2), a great similarity can be observed between Imperatriz and Luiza cultivars, reinforcing the already known genetic relationship between both as reported by Denardi et al (2019b). However, it is also observed that Luiza cultivar showed greater genetic similarity to the group of Venice and Baronesa cultivars, and not to the group that includes the cultivar Cripps Pink.…”
Section: Tl Brancher Et Alsupporting
confidence: 59%
See 1 more Smart Citation
“…The Epagri apple selections and the apple cultivar 'SCS426 Venice' were characterized by the presence of two S-alleles (Table 4), and this presence is consistent with the possibility of those S-alleles having been inherited from their parents, Imperatriz (♀) and Baronesa (♂) (Denardi et al 2019c). Two S-alleles were also found for the selections 141/38 (S 2 S 9 -the S 9 is from the parental 'Baronesa' and the other S-allele is from open pollination), M-1/07 (S 3 S 5 ), M-21/08 (S 3 S 5 ), M-23/07 (S 3 S 5 ), M-4/09 (S 1 S 3 ), M-44/08 (S 1 S 5 ), M-53/08 (S 3 S 19 ), M-58/07 (S 5 S 9 ), M-9/07 (S 3 S 19 ), and the cultivar SCS426 Venice (S 3 S 9 ).…”
Section: Resultssupporting
confidence: 54%
“…de macieira com colheita precoce -02/fevereiro -e resistente à mancha foliar de Glomerella (Colletotrichum gloeosporioides). Produz frutos com ótima qualidade visual, bom sabor e boa textura de polpa, com capacidade de conservação similar à 'Galaxy' quando colhidos no mesmo estágio de maturação (DENARDI et al, 2019a).…”
unclassified